Effects of immersion bathing in Lactobacillus plantarum CLY-05 on the growth performance, non-specific immune enzyme activities and gut microbiota of Apostichopus japonicus. - Bin Li; Jinjin Wang; Jianlong Ge; Meijie Liao; Xiaojun Rong; Jinyan Wang; Yingeng Wang; Zheng Zhang; Chunyuan Wang; Yongxiang Yu (PLoS ONE)
In order to study the optimal use of Lactobacillus plantarum in sea cucumber (Apostichopus japonicus), 49 days feeding trial was conducted to determine the influence of immersion bathing in different concentrations of Lactobacillus plantarum CLY-05 on body weight gain rate and non-specific immune activities. The potential effect of CLY-05 on gut microbiota was also analyzed during the immersion bathing at the optimum concentration. The results showed that the body weight growth rate of all bathing groups was higher than that of control. The highest specific growth rate (4.58%) and weight gain rate (25.35%) was achieved at the bacterial concentration of 1×103 CFU/mL. The activities of non-specific immune enzymes (ACP, AKP, SOD and LZM) of all bathing groups increased after immersion bathing, and the enzyme activities of groups bathed with the bacterium at 1×103 and 1×104 CFU/mL reached the highest. Therefore, 1×103 CFU/mL was considered as the optimum concentration of L. plantarum CLY-05 for A. japonicus pond culture. The results of gut microbiota analysis showed that the gut microbiota changed with the addition of L. plantarum CLY-05, and the richness and diversity of the gut microbiota peaked on day 14 and day 21, respectively. The correlation analysis revealed that the non-specific immune enzyme activities were significantly correlated to some gut bacteria (in the phyla Proteobacteria, Firmicutes) after immersion bathing in L. plantarum CLY-05. These findings provide the theoretical foundation for probiotic application in sea cucumber farming.